Local gene expression in nerve endings. Issue 3 (17th September 2013) - Crispino, Marianna; Chun, Jong Tai; Cefaliello, Carolina; Capano, Carla Perrone; Giuditta, Antonio; Sotelo‐Silveira, José R.; Holt, Christine E.
ABSTRACT At the Nobel lecture for physiology in 1906, Ramón y Cajal famously stated that "the nerve elements possess reciprocal relationships in contiguity but not in continuity, " summing up the neuron doctrine. Sixty years later, by the time the central dogma of molecular biology formulated the axis of genetic information flow from DNA to mRNA, and then to protein, it became obvious that neurons with extensive ramifications and long axons inevitably incur an innate problem: how can the effect of gene expression be extended from the nucleus to the remote and specific sites of the cell periphery? The most straightforward solution would be to deliver soma‐produced proteins to the target sites. The influential discovery of axoplasmic flow has supported this scheme of protein supply. Alternatively, mRNAs can be dispatched instead of protein, and translated locally at the strategic target sites. Over the past decades, such a local system of protein synthesis has been demonstrated in dendrites, axons, and presynaptic terminals. Moreover, the local protein synthesis in neurons might even involve intercellular trafficking of molecules. The innovative concept of glia‐neuron unit suggests that the local protein synthesis in the axonal and presynaptic domain of mature neurons is sustained by a local supply of RNAs synthesized in the surrounding glial cells and transferred to these domains. Here, we have reviewed some of the evidence indicating the presence of a local system of protein synthesis in axon terminals, and have examined its regulation in various model systems. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 74: 279–291, 2014